Phase 1 study of the Aurora kinase A inhibitor alisertib (MLN8237) combined with the histone deacetylase inhibitor vorinostat in lymphoid malignancies. Issue 2 (28th January 2020) - Siddiqi, Tanya; Frankel, Paul; Beumer, Jan H.; Kiesel, Brian F.; Christner, Susan; Ruel, Chris; Song, Joo Y.; Chen, Robert; Kelly, Kevin R.; Ailawadhi, Sikander; Kaesberg, Paul; Popplewell, Leslie; et al.
Abstract: Alisertib, an Aurora kinase A inhibitor, was evaluated in a Phase 1 study in combination with the histone deacetylase inhibitor vorinostat, in patients with relapsed/refractory lymphoid malignancies ( N = 34; NCT01567709). Patients received alisertib plus vorinostat in 21-day treatment cycles with escalating doses of alisertib following a continuous or an intermittent schedule. All dose-limiting toxicities (DLTs) were hematologic and there were no study-related deaths. The recommended phase 2 dose (RP2D) of the combination was 20 mg bid of alisertib and 200 mg bid of vorinostat on the intermittent schedule. A 13-patient expansion cohort was treated for a total of 18 patients at the RP2D. There were no DLTs at the RP2D, and toxicities were mainly hematologic. Two patients with DLBCL achieved a durable complete response, and two patients with HL achieved partial response. Alisertib plus vorinostat showed encouraging clinical activity with a manageable safety profile in heavily pretreated patients with advanced disease.